Peningkatan pemahaman guru tentang pengamanan data ajar melalui pelatihan online di SMPN I Karangwelas - Ranggi Praharaningtyas Aji; Muhamad Awiet Wiedanto Prasetyo; Argiyan Dwi Pritama; Ika Ayu Pratiwi; Resti Nur Azizah (Universitas Hamzanwadi, 2021)
The importance of securing data is something that most Indonesian teachers ignore. In addition, their inability to secure data is also a factor supporting the failure to secure data. Allowing access to their personal computers to be known and the loss of data due to viruses is often experienced by teachers at SMPN 1 Karanglewas. For this reason, training is made that is packaged in a teaching data security webinar. This activity aims to grow the understanding and awareness of teachers in securing the teaching data they have. The implementation of this activity uses Google Meet technology, which can be accessed directly through the YouTube channel. The results obtained are the increasing understanding of the teachers seen from the difference in the results of the post-test and pre-test, which reaches 40-80%. In addition, there were also positive responses from the teachers participating in the webinar, which stated that 56% of the participants stated that it was good and 30% was sufficient, and 24% was excellent. The next activity that is expected to be carried out is live class making training and the manufacture of interactive teaching materials.